Large innovating firms and patent management: Challenges for SMEs’ managers and IP officials in catching-up economies - Mendonça, S. (Journal of Intellectual Property Rights, 2005)
Intellectual property management has become a centrepiece of global corporate strategy. A key characteristic of large innovating firms today is the diversified nature of their technology portfolio. Patents in new generic technologies such as information & communication technologies, drugs & biotechnology and new materials have soared since the early 1980s. This is also true for unrelated industries, a phenomenon known as technological diversification. This paper focuses on the evolution of empirical patterns in patenting by the largest industrial companies from Europe, Japan and the US. Implications of this multi-technology trend for IP offices and small and medium-sized firms from catching-up countries are explored.